Comparative metabolism of tramadol and tapentadol: a toxicological perspective - Barbosa, J (2016)
Tramadol and tapentadol are centrally acting, synthetic opioid analgesics used in the treatment of moderate to severe pain. Main metabolic patterns for these drugs in humans are well characterized. Tramadol is mainly metabolized by cytochrome P450 CYP2D6 to O-desmethyltramadol (M1), its main active metabolite. M1 and tapentadol undergo mainly glucuronidation reactions. On the other hand, the pharmacokinetics of tramadol and tapentadol are dependent on multiple factors, such as the route of administration, genetic variability in pharmacokinetic components and concurrent consumption of other drugs. This review aims to comparatively discuss the metabolomics of tramadol and tapentadol, namely by presenting all their known metabolites. An exhaustive literature search was performed using textual and structural queries for tramadol and tapentadol, and associated known metabolizing enzymes and metabolites. A thorough knowledge about tramadol and tapentadol metabolomics is expected to provide additional insights to better understand the interindividual variability in their pharmacokinetics and dose-responsiveness, and contribute to the establishment of personalized therapeutic approaches, minimizing side effects and optimizing analgesic efficacy.